Epidemiology of rotavirus gastroenteritis and need of high rotavirus vaccine coverage with early completion of vaccination schedule for protection against rotavirus diarrhea in India: A narrative review - Bhaskar Raju; Raunak P Parikh; Volker V Vetter; Shafi Kolhapure (Wolters Kluwer Medknow Publications, 2019)
Rotavirus is a leading cause of severe pediatric diarrhea worldwide, with about 199,000 childhood deaths in 2015, of which 90% in low-income countries. India alone accounts for 22% of the global rotavirus gastroenteritis (RVGE)-related deaths among children below 5 years of age. The World Health Organization recommends introducing rotavirus vaccines (RVVs) as a priority in developing countries where high rates of RVGE are observed. To have the desired impact, RVV should be administered the earliest possible, ideally before the first episode of RVGE. In India, four RVVs are available for use in infants ≥6 weeks of age: the single-strain, two-dose, live-attenuated human RVV Rotarix; the five-strain, three-dose, human-bovine reassortant RVV Rotateq; the single-strain, three-dose, naturally reassortant human-bovine RVV Rotavac; and the five-strain, three-dose, human-bovine RVV Rotasiil; all of them proven to be efficacious and well tolerated. Whereas Rotarix and Rotateq have shown high efficacy/effectiveness against severe RVGE in developed countries (≥90%), they have been observed to be lower in developing countries (~40%-70%). Rotavac and Rotasiil have shown similar efficacy in low-income settings, but further studies are needed to assess their effectiveness. Rotarix and Rotateq have not shown increased intussusception (IS) risk in clinical trials. Postmarketing surveillances were able to show a very tiny increased risk of IS after the first dose of vaccine, but the extensive benefits of rotavirus vaccination far outweigh the low-level risk of IS. In India, where the disease is a major problem and occurs in very early months of life, RVVs should have high coverage and vaccination schedule should be completed as early as possible (≥6 weeks of age) to maximize the vaccine impact.